PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA IPS KELAS IV DI SD NEGERI 017 RANAH SINGKUANG - Nikmatul Husnah; Hendri Marhadi; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research was motivated by the lack of student learning achievement with an average value of 60,34. This research was aimed to improve student learning achievement of IPS for the fourth grade students of SD Negeri 017 Ranah Singkuang with the application of cooperative learning model talking stick. Design research is action research (CAR), which was implemented in two cycles. Each cycle consists of two meetings and one-time delivery of materials meeting the daily tests. The research was carried out in April the number of 29 students consisting of 19 male and 10 female. To be successful class action research, the researchers set the stage that action planning, action, observation and reflection. The data collection instrument of observation and achievement test, data analysis technique that is used as follows, namely Activity Teacher, teacher activities meeting I 62,50% to the category of enough, Meeting II 74,0% with good category, 83,3% of the IV Meeting of the very good category, 91,67% V Meeting with very good category. Students activities at the meeting of the first meeting of 54,17% to the category of low, Meeting II 66,67% with enough categories, Meeting IV 79,17% with good category, Meeting V of 87,50% with a very good category. Improved learning outcomes of the student base score is 60,34 increased to 75,0 (14,66%), the first increase in the Daily Deuteronomy Daily II to 81,9 (21,56)%. From this research, the conclusion that by implementing cooperative learning model talking stick can improve learning outcomes IPS for the fourth grade students of SD Negeri 017 Ranah Singkuang.Keywords: The Implementation of Cooperative Learning Model The Type of Talking Stick, Learning Achievement of IPS